2015
DOI: 10.2308/jfir-51329
|View full text |Cite
|
Sign up to set email alerts
|

Do Compustat Financial Statement Data Articulate?

Abstract: Using the Financial Statement Balancing Model (FSBM) from Compustat, we examine whether financial statement data articulate for 10,681 U.S. nonfinancial firms for 24 years, a total of 92,951 firm-years. We accomplish three research goals. First, we build the first formal model of financial statement articulation, providing a benchmark for subsequent discussions of articulation. Second, we show how to handle missing data to ensure articulation, by either filling in zeros or inferring the missing data using othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…These are either reported as zero, aggregated with other items in the financial reports or reported but not found by Compustat. We follow the practice of setting these to zero, relying on the finding in Casey et al (2016) that setting to zero satisfies certain articulating accounting equations 82.7% of the time. Nevertheless, the remaining 17.3% are a qualification to our analysis.…”
Section: Calculation Of Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…These are either reported as zero, aggregated with other items in the financial reports or reported but not found by Compustat. We follow the practice of setting these to zero, relying on the finding in Casey et al (2016) that setting to zero satisfies certain articulating accounting equations 82.7% of the time. Nevertheless, the remaining 17.3% are a qualification to our analysis.…”
Section: Calculation Of Variablesmentioning
confidence: 99%
“…We follow the practice of setting these to zero, relying on the finding in Casey et al. (2016) that setting to zero satisfies certain articulating accounting equations 82.7% of the time. Nevertheless, the remaining 17.3% are a qualification to our analysis.…”
Section: The Datamentioning
confidence: 99%
“…We propose an earnings forecast model using the Standard and Poor's (S&P) Compustat database items that Casey et al (2016) show coincide with Compustat OIADP. We denote the names of items reported in financial statements in lowercase and the names of Compustat items in uppercase, for example, cogs in an income statement versus COGS in Compustat.…”
Section: Introductionmentioning
confidence: 99%
“…We utilize the SALE (net sales revenue), COGS (cost of goods sold), DP (total depreciation and amortization), and XSGA (selling, general, and administrative expenses) to predict OIADP (operating income after depreciation and amortization). Casey et al (2016) show that Equation (1) generally holds in Compustat for each company in every year and quarter: OIADP = SALE − COGS − DP − XSGA (1) Anderson et al (2003) (hereafter, "ABJ") found that XSGA is a mixture of fixed and variable costs that, on average, increase more for a 1% increase in the SALE than they decrease for a 1% decrease in the SALE and thereby exhibit "sticky" cost behavior. Shust and Weiss (2014) show that depreciation is also a sticky accrual accounting cost.…”
Section: Introductionmentioning
confidence: 99%
“…For example, more nuanced differences arise in applying free cash flow analysis where it is not always apparent if an item in the balance sheet or cash flow statement constitutes an actual cash flow relevant to a firm's intrinsic value. In fact, the changes in both statements do not always agree (e.g., Casey et al., 2015; Hribar et al., 2002; Wilkins & Loudder, 2000). Further, Penman (2006), discusses the imprecise assumptions that are used in most valuation models.…”
Section: Introductionmentioning
confidence: 99%